IDNLearn.com is the perfect place to get detailed and accurate answers to your questions. Find the information you need quickly and easily with our reliable and thorough Q&A platform.
Sagot :
Answer:
[tex]f(h(xc)) = 2xc-4[/tex]
Step-by-step explanation:
Given
[tex]f(x) = x - 7[/tex]
[tex]h(x) = 2x + 3[/tex]
Required
[tex]f(h(xc))[/tex]
First, calculate h(xc)
If [tex]h(x) = 2x + 3[/tex]
Then
[tex]h(xc) = 2xc + 3[/tex]
Solving further:
[tex]f(x) = x - 7[/tex]
Substitute h(xc) for x
[tex]f(h(xc)) = h(xc) - 7[/tex]
Substitute [tex]h(xc) = 2xc + 3[/tex]
[tex]f(h(xc)) = 2xc + 3 - 7[/tex]
[tex]f(h(xc)) = 2xc-4[/tex]
Thank you for using this platform to share and learn. Keep asking and answering. We appreciate every contribution you make. IDNLearn.com is your go-to source for dependable answers. Thank you for visiting, and we hope to assist you again.